The Role and Teacher's Understanding in Implementing Curriculum on Vocational High School - Riana Nurmalasari; Blima Oktaviastuti; Annisau Nafiah (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2019)
This study aims to describe the teacher's understanding and how teacher’s role in the implementation of the 2013 curriculum. This research uses a descriptive qualitative research design with case study. Research data supported by research tools in the form of audio-visual and field notes. The informants are the headmaster, the vice minister of curriculum, teachers, and students who carry out learning using the 2013 curriculum at SMK 1 Kertosono. Based on the results of the analysis, it is known that the understanding of teachers is not so fully understood the 2013 curriculum as a whole. The role of teacher for implementation of the 2013 curriculum conducted by teachers including: (1) Planning, teachers in making learning plans based on the results of teacher group discussions conducted between teacher peers and the internet; (2) Implementation, the implementation of learning conducted by the teacher includes three activities, namely the introduction, main, and closing activities; and (3) Assessments, assessments made by teachers are authentic assessments, which include; assessment of attitudes, knowledge and skills.